Multilayered Equivalent Finite Element Method for Embedded Honeycomb Plates - Yang Xu; Haohui Wang; Xiaowei Sheng (Shock and Vibration)
To investigate the mechanical properties of embedded honeycomb plates with high efficiency and accuracy, a new multilayered equivalent finite element method (FEM) model is proposed. A series of FEM numerical studies (modal analysis, static analysis, and shock spectrum analysis) are performed. The goal is to compare the errors produced by the multilayered equivalent method and by existing equivalent approaches. The obtained results indicate that the proposed model shows good agreement with the original plate. Moreover, based on the new model, a parametric study correlating the microstructure parameters (embedded depth/cell size) to modal frequency is proposed, and a multiparameter equation for frequency and embedded depth/cell size is established to serve as a basis for structural optimization design.